Ybor City : crucible of the Latina South - McNamara, Sarah, 1987- (Justice, power, and politics., 2023)
"When we think about the origins of Cuban immigration to the United States, we often imagine the anti-Communist exiles who fled the regime of Fidel Castro and settled in South Florida during the 1950s and 1960s. But before Miami became Havana USA, a wave of leftist, working-class migrants from prerevolutionary Cuba crossed the Florida Straits and made Ybor City the center of the immigrant South and the global capital of the Cuban cigar industry. Located on the eastern edge of Tampa, a port city along Florida's Gulf Coast, Ybor was a multiracial, multiethnic neighborhood where radical thinkers and laborers found work and refuge against the shifting tides of international political turmoil during the early half of the twentieth century. In this book, Sarah McNamara tells the story of how immigrant women ensured and fought for community survival across generations and against the backdrop of a post-Confederate, Jim Crow-controlled southern order"--Provided by publisher.